Guided versus non-guided chin repositioning: a retrospective study on accuracy - Gorla, Luis Fernando de Oliveira [UNESP] (2024)
Genioplasty is a widely used surgical approach to address chin deformities by performing an osteotomy on the inferior border of the mandible to allow for comprehensive repositioning of the chin. This study aimed to compare the accuracy of freehand chin repositioning with a guided technique that employed specialised surgical guides. For this retrospective study, data from 30 adult patients who underwent orthognathic surgery to correct dentofacial deformities were analysed. All patients underwent virtual planning before surgery, with half of them treated using freehand chin repositioning and the other half using the guided technique. The surgical outcomes were measured and compared with the virtual plan to assess the positional and rotational accuracy of the techniques. In terms of translational assessment, noteworthy values that exceeded clinically acceptable limits were observed only in sagittal movement in the freehand group (0.97 mm, interquartile range (IQR) 0.73–2.29 mm). Regarding rotational accuracy, both groups exhibited an IQR that surpassed acceptable limits for pitch (3.26°, IQR 2.06–5.20 for the guided group and 2.57°, IQR 1.63–4.24° for the freehand group). The Mann-Whitney test indicated no statistical differences between the groups in any translational or rotational assessment. In conclusion, although there was no statistical difference, the guided technique proved effective in achieving clinically acceptable accuracy in all positions and almost all rotations, displaying superior results in sagittal positioning compared with the freehand technique. To fully harness the advantages of guides and to guarantee accuracy in all rotations, we recommend further research involving guides made of more rigid materials, and customised implants.